Pengaruh Desentralisasi Fiskal dan Kinerja Terhadap Akuntabilitas Pelaporan Keuangan Pemerintah Daerah di Indonesia: Efek Moderasi dari Kinerja - Kurniatul Mudhofar; Afrizal Tahar (Journal of Accounting and Investment, 2016)
The purpose of this study is to examine the effect of fiscal decentralization which is proxied by independence of local government, dependence on the central government, effectiveness of regional revenue realization, and performance toward local government financial reporting accountability. The sample using 698 district/city are listed in the Dirjen Perimbangan Keuangan Pusat dan Daerah Kementrian Dalam Negeri. The analysis technique used for Hypotheses testing is ordinal logistic regression. The results reveal independence of local government and performance influence degree of local government financial reporting accountability. Two variables i.e. dependence on the central government and effectiveness do not influence local government financial reporting accountability. While the performance as the moderating variable only influence on the relationship between dependence on the central government and local government financial reporting accountability and has no influence on the relation between region's autonomy relation and local government financial reporting accountability.